If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = (x + 3)(x + 6) Reorder the terms: y = (3 + x)(x + 6) Reorder the terms: y = (3 + x)(6 + x) Multiply (3 + x) * (6 + x) y = (3(6 + x) + x(6 + x)) y = ((6 * 3 + x * 3) + x(6 + x)) y = ((18 + 3x) + x(6 + x)) y = (18 + 3x + (6 * x + x * x)) y = (18 + 3x + (6x + x2)) Combine like terms: 3x + 6x = 9x y = (18 + 9x + x2) Solving y = 18 + 9x + x2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 18 + 9x + x2
| X+11=(X^2-26X+169)/2 | | (4v-7)(1+v)=0 | | y^2+19y+90.25=12.25 | | SA=5*4+8*5+8*4+8*3 | | =5*4+8*5+8*4+8*3 | | 5*4+8*5+8*4+8*3=s | | 5x^2-14xy-24y^2= | | L=b+c/2 | | 10+4x-5x^2=0 | | 5*4+8*5+8*4+8*3= | | y-7=10x(-6x+10)-10x^2+6 | | -16t^2+76t+46=0 | | 8b+1+6b=-3b+6 | | 8x-11=16x | | p-22=31/4(h-18) | | 6t+3(2+9t)=7 | | -16t^2+50t+10=0 | | 200x-x^2=8400 | | 60-2P=0 | | p-18=31/4(h-7) | | -16t^2+32t+300=h(t) | | 2x/5=14 | | 2x-9y=2 | | 6=3y+x | | p-22=31/4(h-7) | | 5-7x=y | | 0=100x-19x-23 | | -3+u=-4 | | 18X^3-15x^2-12x+9=0 | | x^2+14x-370=0 | | ((36x^5)-(28x^4))/4x^2 | | 2x+3=11x-24 |